Participatory approaches: a facilitator's guide - and VSO (VSO, 2004)
This book provides a set of guidelines for people who will be involved in participatory processes and projects with specific design focus on VSO (Voluntary Services Overseas) volunteers. It looks at appropriate levels of participation; pitfalls of participatory approaches (PA); best practice in facilitation; and tools for participation. The guide is organised into three parts (I) Principles, (II) Methods and (III) Toolkit. Part I gives a background to PA with a comparative analysis of PA in relation to top-down approaches, and within the range of PAs; looks at the role PA in VSO; discusses how to facilitate participatory processes with multiple stakeholders; presents a framework for PA on different levels of participation; and examines key facilitation skills needed to support participatory activities. Part II collates a range of participatory methods that have been used successfully in the field by VSO volunteers. Methods are categorised according to this suitability for use at different stages of a project process. Examples are also given of methods that can be used for specific purposes, such as participatory organisational appraisal and gender/diversity analysis. Part III gives tips on how to choose the most appropriate tool and how to organise participatory workshops and small group activities. It also systematically records a range of tools used by development workers all over the world with reference to what tool is appropriate in what situation. A profile of each tool includes guidelines on its purpose, potential applications and variations, as well as possible pitfalls. Illustrative case studies taken form real experiences of development workers in the field are also included.